The Strategic Management In Improving Global Competitiveness At State Madrasah: A Quantitative Swot Analysis - Marno, Marno; Sonia, Nur Rahmi; Haris, Abdul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This research aims to determine the principal's strategy in realizing madrasa competitiveness through an analysis of Strengths, Weaknesses, Opportunities and Threats (SWOT) at Madrasah Aliyah Negeri 2 Ponorogo. This study employed a qualitative approach using a case study research design. Data was collected through in-depth interviews, observation and documentation. Source triangulation and technical triangulation were used to ensure the validity and reliability of the data. Data analysis was carried out by referring to the concepts of Milles, Huberman and Saldana; data collection, data condensation, data presentation and drawing conclusions. The research results show that the head of Madrasah Aliyah Negeri 2 Ponorogo has implemented well strategic management in achieving madrasa competitiveness. This is proven by the achievement of madrasa targets in accordance with the prepared plans. Apart from that, it can be seen from the results of the Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis through detailed internal and external factor analysis in the Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices. The results of the matrix shows that Madrasah Aliyah Negeri 2 Ponorogo is in quadrant 1. This position shows that the madrasa is in development and growth position. Therefore, Madrasah Aliyah Negeri 2 Ponorogo is advised to use a progressive strategy by utilizing the internal strengths of the madrasah to take advantage of opportunities so that the madrasah's global competitiveness is realized.